A Comparison of Two Teaching Strategies Lecture vs. Discussion in a Small Class Environment at Florida Southern College - Byers, William S.; Hedrick, Robert E.; Florida Southern Coll., Orlando. McCoy Extension Center ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1976)
Results of an experiment conducted to compare two teaching strategies showed somewhat higher test scores for college students taught by the lecture method, while students taught by the discussion method evinced higher interest and attendance. The experiment consisted of two sections of a night class in Social Psychology which were taught simultaneously, one by the lecture method, and the other by the discussion method. The sections were composed of students of relatively equal ability and were jointly taught by two professors. Identical and comprehensive examinations were used to evaluate competency achieved. A mixed teaching strategy employing both lecture and discussion is recommended, along with further research on the long range effects of the two methods. (STS)
Educational level discussed: Higher Education.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Academic Achievement; Comparative Analysis; Discussion (Teaching Technique); Evening Students; Grouping (Instructional Purposes); Higher Education; Lecture Method; Student Attitudes; Student Characteristics; Student Motivation; Teaching Methods; Reports, Research